Triangular Microstrip Patch Antenna with Back-to-Back Structure to Obtain Bi-Directional Radiation Pattern - Muhammad Ikhsan Apriadi.H; Muh. Wildan; Teguh Firmansyah (Indonesian Journal of Education and Mathematical Science, 2023)
In this research, a triangular patch microstrip antenna with a back-to-back structure technique has been designed to obtain Bidirectional radiation patterns operating at a frequency of ADSB 1090 MHz. The back-to-back structure technique using 2 substrate layers stacked together to form a single microstrip antenna component. As a result, the antenna has 2 patches on both sides of the microstrip, and the feedline is located between the 2 substrate layers. This antenna was designed using simulation software with an FR-4 substrate material. The parameter values obtained from the simulation at a frequency of 1090 MHz are: Return loss -15.4 dB, VSWR 1.4, Bandwidth 17.2 MHz, and Impedance 46.02 â„¦.